Author Correction: Hypervirulent Listeria monocytogenes clones’ adaptation to mammalian gut accounts for their association with dairy products - Mylène M. Maury (Nature Portfolio, 2019)
An amendment to this paper has been published and can be accessed via a link at the top of the paper.